2010
DOI: 10.1021/es102334u
|View full text |Cite
|
Sign up to set email alerts
|

Trend Reversal of Nitrate in Danish Groundwater - a Reflection of Agricultural Practices and Nitrogen Surpluses since 1950

Abstract: This paper assesses the long-term development in the oxic groundwater nitrate concentration and nitrogen (N) loss due to intensive farming in Denmark. First, up to 20-year time-series from the national groundwater monitoring network enable a statistically systematic analysis of distribution, trends, and trend reversals in the groundwater nitrate concentration. Second, knowledge about the N surplus in Danish agriculture since 1950 is used as an indicator of the potential loss of N. Third, groundwater recharge C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
71
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(80 citation statements)
references
References 33 publications
8
71
1
Order By: Relevance
“…The present paper continues the analysis initially presented and published in Hansen et al (2011). The focus is still on nitrate in the oxic zone of the Danish groundwater, because we are examining the effect of nitrate leaching on groundwater nitrate concentrations.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…The present paper continues the analysis initially presented and published in Hansen et al (2011). The focus is still on nitrate in the oxic zone of the Danish groundwater, because we are examining the effect of nitrate leaching on groundwater nitrate concentrations.…”
Section: Introductionmentioning
confidence: 71%
“…Since the 1980s, agriculture in Western Europe has managed to reduce its nitrogen surpluses, owing to stringent national and European community policies (Vitousek et al, 2009;Grizzetti et al, 2011;Hansen et al, 2011;Dalgaard et al, 2012). However, Vitousek et al (2009) reckon that regions in Africa continue to extract the nutrient capital of what were once highly fertile soils with low yields, while in contrast intensive agricultural production in Northern China has a very high input of N to agricultural fields and high yields, but also a very high N loss to the environment.…”
Section: Introductionmentioning
confidence: 99%
“…As pointed out in many studies (Böhlke and Denver, 1995;Ruiz et al, 2002a;Worrall and Burt, 2001), soils are able to store N, leading to poor correlations between N losses from agricultural soils and headwater quality. Consequently, N leaching is affected by past land use and management practices (Hansen et al, 2011(Hansen et al, , 2012, which varied a lot in this area during the past 300 yr (Caspersen and Fritzbøger, 2002), but a further study of this aspect was out the scope of the present study. Furthermore, the NO − 3 stored in soils can be released into sub-surface and groundwater after some time.…”
Section: Nitratementioning
confidence: 95%
“…Analysis of lag times required for improvements of groundwater nitrate levels in Ireland showed that the achievement of good water quality status for some water bodies may be too optimistic but improvements are predicted within subsequent 6-and 12-yr cycles (Fenton et al, 2011). Analyzing a 50 yr time series of SNB and nitrate concentration in groundwater in Denmark, Hansen et al (2011) found that nitrate concentrations have been decreasing since 1980. They found that the frequency of downward nitrate trends in groundwater samples clearly increased with lower recharge age, providing proof that younger groundwater responds fastest to decreasing trends of SNB.…”
Section: Water Qualitymentioning
confidence: 99%